Theology of Baku Kele: A Contextual Constructive Theology for A Post-Communal Conflict - Rouli Retta Trifena Sinaga; Johan Robert Saimima (Sekolah Tinggi Teologi Intheos Surakarta, 2023)
After communal conflict happened in Maluku in 1999-2004, Larike’s Christian society hasproblematic social relationship with Larike’s Moslem society. Baku kele as a cultural fraternal wisdom of Larike’s society is rarely donein Larike. Therefore, through this paper we try to offer theology of baku kelefor them. By understanding baku keletheologically as care to others and social lifestyle, this will have implications for social relationship reconstruction carried out by The Protestant Church of Maluku in Larike. Here the theology of baku keleis constructed from stories of communal conflict effects to Larike’s Christian society conveyed by them, cosmological view of Larike’s society,biblical basis of Luke 10:25-37, and some contemporary theological ideas.This paper is to propose a small contribution to The Protestant Church of Maluku’s contextual theology forrestoring social relationship post-communal conflict through an open existence continually.